Successful Percutaneous Thoracic Duct Embolization for Chylothorax After Total Arch Replacement - Fumihiro Kitashima, MD; Naohiro Shimada, MD; Yojiro Machii, MD; Masashi Tanaka, MD, PhD (Texas Heart Institute Journal, 2024)
Chylothorax after cardiac surgery is a rare complication associated with severe morbidity and mortality. This report documents successful treatment with percutaneous thoracic duct embolization for chylothorax after total arch replacement. A 69-year-old man underwent replacement of the aortic arch to treat a ruptured aortic aneurysm. After surgery, the left thoracic drain discharged 2,000 to 3,000 mL serosanguineous fluid per day, even though the patient took nothing orally and was administered subcutaneous octreotide therapy. On postoperative day 9, percutaneous thoracic duct embolization was performed, and the drain could be removed. The chylothorax did not recur, and the patient was discharged on postoperative day 17.